Misuse of OTC drugs in Poland. Issue 8 (August 2016) - Zaprutko, Tomasz; Koligat, Dorota; Michalak, Michał; Wieczorek, Marta; Józiak, Malwina; Ratajczak, Monika; Szydłowska, Kinga; Miazek, Joanna; Kus, Krzysztof; Nowakowska, Elżbieta
Highlights: Misuse of OTC drugs became an important public health concern in Poland. Theoretically safe drugs may lead to serious side effects. There are discrepancies between the restrictive law and common practices in Polish pharmacies. Drugs containing controversial substances should be moved into prescription status. Abstract: Introduction: The misuse of over-the-counter (OTC) drugs became a global public health concern. Although abuse with dextrometorphan (DXM), pseudoefedrine (PSD), codeine (COD) or benzydamine (BND) may lead even to psychosis, drugs containing these substances are relatively cheap and freely available. In Poland the Act on Counteracting Drug Addiction was amended in 2015, however it seems that there are still some points which could be improved. Methods: Study was conducted between October 2014 and June 2015 using a specially designed questionnaire delivered to pharmacists from the Greater Poland region. Questionnaire consisting of 11 closed questions was distributed by direct contact and via the Internet. From over 2500 distributed questionnaires, we received 761 sheets and 680 were included. Results: The misuse of OTC drugs is increasing in Poland from pharmacists point of view. The most popular substance was PSD followed by COD and DXM. The main reason of misuse of these drugs could be related to the use of Internet and free access to these medications. In respondents (58.2%) opinion OTC drugs containing analyzed substances should be moved into the prescription status. Conclusions: The misuse of OTC drugs should be considered as a very dangerous phenomenon. Although the Act on Counteracting Drug Addiction was amended in Poland in 2015, there are some facets requiring improvement. Social education may play a key role in the limitation of misuse of OTC drugs.